2006
DOI: 10.1007/s00438-006-0134-8
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, comparative characterization of porcine SCAP gene, and identification of its two splice variants

Abstract: Sterol responsive element binding protein (SREBP) cleavage-activating protein (SCAP) is the key regulator of activation of SREBPs, which stimulate most enzymes in cholesterol and lipid synthesis. In order to investigate the molecular basis of lipid metabolism in the pig, a unique model for fat deposition, we isolated and characterized the porcine SCAP. The 4,096-bp full-length porcine SCAP cDNA contains an open reading frame of 3,840 bp. The predicted SCAP protein consists of 1,280 amino acids of 55-92% identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Initially, primer sets were used for each of these genes in order to amplify PCR fragments from each gene. SREBF1 primer set (Table 1) was designed from the corresponding human SREBF1 exon 6 genomic sequence, SCAP primer set was described in Qiu et al, (2006) (Forward primer: GCAGCGC-CGGGACAGTGG; reverse primer: TGATGCCC-GAGGCCACCTCCTC) and amplified intron 13 of the SCAP gene. MBTPS1 primers were designed from the consensus regions of exon 5 (Forward primer: TGAAGGAGAGAACCAACTG-GA) and exon 6 (reverse primer: CTGCATCTG-GAGCAAATCCT) of the human (accession numbers in ensemble ENSE00000945694 and ENSE00000945695) and mouse (accession numbers: ENSMUSE00000319523 and ENS-MUSE00000319518) MBTPS1 gene.…”
Section: Molecular Genetic Marker Evaluationmentioning
confidence: 99%
“…Initially, primer sets were used for each of these genes in order to amplify PCR fragments from each gene. SREBF1 primer set (Table 1) was designed from the corresponding human SREBF1 exon 6 genomic sequence, SCAP primer set was described in Qiu et al, (2006) (Forward primer: GCAGCGC-CGGGACAGTGG; reverse primer: TGATGCCC-GAGGCCACCTCCTC) and amplified intron 13 of the SCAP gene. MBTPS1 primers were designed from the consensus regions of exon 5 (Forward primer: TGAAGGAGAGAACCAACTG-GA) and exon 6 (reverse primer: CTGCATCTG-GAGCAAATCCT) of the human (accession numbers in ensemble ENSE00000945694 and ENSE00000945695) and mouse (accession numbers: ENSMUSE00000319523 and ENS-MUSE00000319518) MBTPS1 gene.…”
Section: Molecular Genetic Marker Evaluationmentioning
confidence: 99%
“…SREBP cleavage-activating protein ( SCAP ) is a family of endoplasmic reticulum (ER) membrane-bound transcription factors required for cleavage and activation of sterol regulatory element-binding proteins (SREBPs), which play a critical role in the regulation of cholesterol homeostasis (Weber et al 2004). To date, SCAP gene has been cloned and characterised from several vertebrate (Qiu et al 2006) and non-vertebrate species (Seegmiller et al 2002). Several studies have confirmed that the single nucleotide polymorphisms (SNPs) in SCAP might affect intracellular lipid metabolism (Iwaki et al 1999), metabolic phenotypes (Cao et al 2002), and obesity (Liu et al 2014).…”
mentioning
confidence: 99%